BLENDED LEARNING IN MEDICAL INSTITUTIONS OF HIGHER EDUCATION - Nalyvaiko, Natalya; Nalyvaiko, Oleksii (Educological discourse, 2021)
The article considers the main provisions of blended learning organization in medical institutions of higher education. The main online platforms and digital teaching aids, that are used in medical institutions of higher education during the educational process based on blended learning, are identified in particular: distance learning platforms (Equity Maps, Google Classroom, Moodle), mobile-digital applications (Classtime, LearningApps, Quizizz) and online communication platforms (Google Meet, ZOOM, WeBex). The concept of blended learning is defined as a harmonious combination of students’ classwork and the use of information and digital technologies in extracurricular activities (independent work, group work, etc.). The principles of organizing the educational process in institutions of higher medical education include a general didactic approach in working with large groups, discussion in small groups, individual training and learning using information and digital technologies. An important aspect in the training of highly qualified medical professionals in the blended learning format is blended laboratory courses. Such an organization of training, as shown in the study, is popular with both students and teachers of laboratory bachelor courses. Note that in this process, teachers mainly focus on the development of students’ abilities for autonomous learning, and not just on the transfer of theoretical knowledge. The best experience of blended learning usage in the world medical institutions of higher education is considered. The advantages of blended learning in medical students’ preparation are shown. In further scientific research it is planned to study the current experience of organizing blended education of Kharkiv National Medical University in the conditions of adaptive quarantine in the 2020/2021 academic year.